DEVIATION AND ATROPHY OF MIDDLE PHALANX OF HAND FOLLOWING PARTIAL SEPARATION IN SYNDACTYLY PATIENT: THEIR FAULT OR OURS? - Kusuma, Diana Murtiati; Saputro, Iswinarno Doso; Rizaliyana, Sitti; Beta Subakti Nata’atmadja (Jurnal Rekonstruksi dan Estetik, 2018)
Highlights: Complex syndactyly reconstruction presents surgical challenges, often resulting in rotational, angular, and nail deformities post-surgery. The early correction of congenital syndactyly, combined with dorsal rectangular flap usage and full-thickness skin grafts, leads to satisfactory outcomes and reduces the need for multiple surgeries per web Abstract: Introduction: Syndactyly is failure of differentiation in which the fingers fail to separate into individual appendages. It is the most common congenital hand anomaly, with an incidence of 1 in 2,000 to 2,500 live births. Surgical separation of fingers as early as 6 month-old is indicated when syndactyly involves digits of unequal length (i.e., ring and little fingers). Early separation is also required in complex syndactyly and cases of acrosyndactyly. The timing of surgery of all other cases of syndactyly remains somewhat controversial; most suggest surgical correction before age of 18 months, whereas others prefer to wait until after this age. Case Illustration: A 13-year old boy, presented with fusion of all fingers of the right hand at birth. Prior to his current visit, he underwent partial separation of the right fingers at the age of 6 y.o. at a local hospital. Following partial separation, the fingers did not grow normally. Current X-ray showed atrophy and deviation of middle phalanx. We performed separation of syndactyly between index and middle finger, and between fourth and small finger in our hospital. Interdigital webbings are released using local flap and the remaining raw surface is covered using full-thickness skin grafts. On follow up, the patient showed good functional and aesthetic outcome. He is able to write with his right hand with better coordination. Discussion: Complex syndactyly reconstruction is a challenging surgical problem. Common post surgical findings include rotational deformity, angular deformity, and nail deformity. We describe how we have altered our approach in these findings. Conclusion: Congenital syndactyly should be corrected early in life. Careful dissection, the use of a dorsal rectangular flap in combination with 2 volar triangular flaps, and use of full thickness skin grafts ensure a satisfactory outcome and minimize the number of operations per web.